Implementasi Blended Learning Based Saintific Approach on Natural Science Learning Independent - Sianturi, Septriyanti; Simanjuntak, Mariati Purnama (INPAFI (Inovasi Pembelajaran Fisika), 2025)
ABSTRACTThis study aims to determine the implementation of blended learning based on a scientific approach to student independence and learning outcomes, as well as the relationship between independence and learning outcomes in the science material of effort and simple aircraft in class 8th grade junior high school. This research was conducted using the quasi-experimental method of two group pretest-posttest design. The sampling technique used random sampling technique. The data were analyzed using the monova test (maltivariate analysis of variance) and the correlation of independence and student learning outcomes. Based on hypothesis testing, there is a significant difference in students' independence and learning outcomes with the application of blended learning based on the scientific approach in science materials. There is a positive correlation relationship between student learning independence and student learning outcomes, namely 0.498 with a moderate category. The percentage increase in N-gain of student learning independence in the experimental class is 51% with a moderate category and the control class is 22% with a low category. The percentage increase in N-gain of student learning outcomes in the experimental class was 74% with a high category and the control class was 35% with a moderate category.Keywords: Blended learning, approach scientific, learning independed and learning outcomes